Role of parent mediation in children's positive use of the internet - Daud, Azlina (2015)
The Internet places the whole world at children’s fingertips. Children communicate through the Internet, learn through the Internet, and are entertained by the Internet. The Internet brings a lot of opportunities to children; however, if their usage is not managed properly, the Internet can also expose children to risk. This study examines how parents’ roles – in terms of parental mediation (PM) and parental cultural capital (PCC) – can increase the benefits experienced by children who use the Internet. By using four constructs of parental mediation theory (active co-use, interaction restrictions, technical restrictions and monitoring) and two constructs of parental cultural capital theory (attitudes and activities), this study attempts to examine the causal effects of these constructs on children’s positive use (CPU) of the Internet by measuring six dimensions, namely information,communication, entertainment, participation, creativity and expression. This study also looks at the effect of gender moderation, which can alter the strength of causal relationship between the independent variables (PM and PCC) and the dependent variable (CPU of the Internet). The data for this study were collected from 384 schoolchildren aged 9 to 16 years (excluding those aged 12, 15 and 17 due to the fact that they were undertaking the Primary School Evalution Test (UPSR), Lower Secondary Assessment (PMR) and the Malaysian Certificate of Education (SPM) at the time of the study) and 384 parents/guardians in Selangor, Malaysia. Stratified sampling was employed to obtain the sample. Classroom-administered questionnaires were used to collect the data from the schoolchildren, while selfadministered questionnaires were used to collect the data from the parents/guardians. Using structural equation modeling Amos, the results from the path analysis reveal that the PM techniques of “active co-use” and “interaction restrictions” have a significant negative relationship with CPU of the Internet; “technical restrictions”, on the other hand, has a significant positive relationship with CPU of the Internet; meanwhile, “monitoring” has no significant relationship with CPU of the Internet. PCC‘s “attitudes” and “activities” also has no significant relationship with CPU of the Internet. Children’s gender moderated the causal effect of “active co-use”, “interaction restrictions” and “technical restrictions” on CPU of the Internet. In conclusion, PM through “technical restrictions” seems to be a better strategy in promoting CPU of the Internet in Malaysia. Based on the findings of this study, it is recommended that parents pay greater attention to the “technical restrictions” mediation strategy and keep abreast of Internet technologies in order to understand the latest technologies, which will in turn enable them to better filter and monitor their children’s online activities and, ultimately, increase children’s opportunities. PM techniques such as discussing with children the positive and negative aspects of the Internet, remaining nearby while children are online, and restricting children’s activities online are not enough to keep children safe from the risks they are exposed to while using the Internet.